Analisis Kalimat Efektif pada Teks Esai dengan Tema Komunikasi serta Ekspresi pada Website “Kompasiana” Edisi Februari 2025 sebagai Bacaan Edukasi dalam Kehidupan Sosial - Elyna Rafiza Zaliana; Naura Lutfia Fajriani; Angela Merici Tamara Wibowo; Farah Maulida Ayu Zahara; Salma Ayu Aini Zulfa; Asep Purwo Yudi Utomo; Riyadi Widhiyanto; Vina Nur Indah Sari (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
Language reflects the identity of a tribe or region through its speech patterns and structure. With its uniqueness and richness, language conveys messages and hopes. When used in accordance with the speaker's intent, its fulfills its communicative function. A well-constructed sentence not only adheres to grammatical rules but also conveys a clear message and strengthens the argument. This study aims to analyze the use of effective sentences in essay texts and identify the factors that influence their effectiveness, so that readers can clearly understand what the writer has written. This research employs a descriptive qualitative approach and syntactic analysis to examine the use of effective sentences in essay texts on the "Kompasiana" website, February 2025 edition. Data were collected through identification, classification based on the characteristics of effective sentences, and analysis in line with the research objectives. The analysis process includes data selection, identification, and conclusion with the help of data cards. The results of the study show the presence of several ineffective sentences in the essay texts, such as ambiguous phrasing, redundancy, and writing that does not comply with the EYD (Improved Spelling System – Ejaan Yang Disempurnakan) and KBBI (Indonesian Dictionary – Kamus Besar Bahasa Indonesia) rules. This research serves as a medium to convey the researcher's ideas and is also expected to be beneficial as a source of learning and information for readers, helping them write texts that comply with linguistic rules, thus producing high-quality and effective content.